PENDAMPINGAN BLENDED LEARNING BERPUSAT PADA KEMAMPUAN LITERASI DAN NUMERASI BAGI GURU SD - Trimurtini Trimurtini; Nursiwi Nugraheni; Nugraheti Sismulyasih Sb; Galih Mahardika Christian Putra; Kurniana Bektiningsih (Aptekmas Jurnal Pengabdian pada Masyarakat, 2021)
The problems faced by two private schools that have almost the same characteristics, namely SDK Girisonta and SDK Genuk, are implementing distance learning and limited face-to-face learning during the COVID-19 pandemic and preparing AKM (minimum competency assessment) including literacy and numeracy skills. The solution to overcome these problems is blended learning training and mentoring centered on literacy and numeracy skills. The method of implementing the Participatory Action and Learning System method includes awareness, capacity building, mentoring and institutionalization. Teachers' knowledge of blended learning, literacy and numeracy reaches 78 in the good category so they are ready to plan and implement. Learning tools with blended learning and focusing on literacy and numeracy, teachers design and implement them in the classroom during distance learning. Reflection on the results of implementation assistance shows that it is very successful in blended learning (92%), successful in focusing on literacy (81%) and less successful in focusing on numeracy (47%). The suggestion from this community service activity is that the success of blended learning is influenced by the readiness of schools, teachers, parents and students, so good communication and awareness of all parties are needed. Through a variety of electronic learning resources and online games that focus on literacy and numeracy, students accompanied by teachers and parents can learn optimally to develop their potential.